Pemanfaatan Kain Serat Alam Pada Busana Wanita dengan Tren Gaya Hidup "Back to Nature" - Rima Febriani; Adinda Caturludysari; Vira Pritalia (JURNAL RUPA, 2019)
Lifestyle trends “Back to Nature” are now widely adopted by people in Indonesia, especially urban residents who register a healthy and practical lifestyle, using nature-based products, for examples fashion products. As one of the largest sub-sector of the creative industry in Indonesia, the fashion industry has the potential and great contribution in efforts to meet the basic needs of society which can directly impact the country's economy. Although lifestyle can influence trends in clothing needs, the role of the designer is needed to direct and produce a variety of clothing that is in harmony with lifestyle needs that return to nature. To overcome this problem, there is an environmentally friendly method that is currently used by various fashion brands in Indonesia and the trend is the use of natural fibre fabrics in the clothing production process. Many local brand designers respond to this lifestyle by creating clothing based on natural fibre that can be used for daily activities. This study uses a qualitative method with a business opportunity approach. This study presents the background and development of natural fibre fabrics by various fashion brands in Indonesia to become the current trend, especially in the lifestyle of “Back to Nature” for women. The biggest reason is that the adoption of more environmentally friendly methods for the Indonesian fashion industry can provide many broad benefits.